142 Analyzing the Impact of Diabetes on Erectile Function Recovery after Radical Prostatectomy. (1st May 2022) - Martinez, J. Flores; Jenkins, L.C.; Benfante, N.; Nelson, C.J.; Schofield, E.; Mulhall, J.P.
ABSTRACT: Introduction: Diabetes (DM) is a known risk factor for ED. The impact of DM on erectile function recovery (EFR) after radical prostatectomy (RP) is poorly understood. Objective: We aimed to assess the impact of DM on the EFR after RP. Methods: Men who had RP with ≥2 years follow-up constituted the study population. EFR was assessed using International Index of Erectile Function, Erectile Function Domain (EFD) score pre-RP and at 2 years post RP. ADT and radiation therapy before or after RP were exclusions. Demographics, comorbidities, pathological parameters were recorded. We performed univariate and multivariate logistic regression assessments to evaluate predictive factors, including DM, patient age, nerve sparing status (NSS) scored between 1 (preserved) to 4 (resected) for each side, and comorbidity profile, associated with poor EFR post-RP. Results: 2024 men were included. Mean age at RP was 61.3±7.1 years. Median baseline and 2-year EFD scores were 27 (IQR = 19-30), and 13 (IQR = 5-25). 10% had DM with a mean pre-RP hemoglobin A1c of 6.6±1.3%. 44% had hypertension, 51% dyslipidemia, 14.5% obstructive sleep apnea, 5% history of coronary artery disease, 8% were current and 34% former smokers. 38% reported two or more comorbidities pre-RP. Median Gleason sum was 7. Nerves were preserved bilaterally in 77% and unilaterally in 16%. Median NS score was 3 (IQR 2-4). Median EFD scores at 2 years with and without DM were 7 (IQR 3-16), and 14 (IQR 5-25), respectively (p<0.001). At 2 years, in men with and without DM, the proportion with EFD ≥24 was 14% and 32% and EFD ≤10 was 63% and 42% respectively. Conclusion: In our cohort, DM was a significant predictor of lower EFR at 2 years post-RP. Disclosure: Work supported by industry: no.